The tomato Ethylene Response Factor Sl‐ERF.B3 integrates ethylene and auxin signaling via direct regulation of Sl‐Aux/IAA27. Issue 2 (27th April 2018) - Liu, Mingchun; Chen, Yao; Chen, Ya; Shin, Jun‐Hye; Mila, Isabelle; Audran, Corinne; Zouine, Mohamed; Pirrello, Julien; Bouzayen, Mondher
Summary: Plant growth and development is coordinated by complex networks of interacting hormones, and cross‐talk between ethylene and auxin signaling is essential for a wide range of plant developmental processes. Nevertheless, the molecular links underlying the interaction between the two hormones remain poorly understood. In order to decipher the cross‐talk between the Ethylene Response Factor Sl‐ERF.B3 and Sl‐IAA27, mediating ethylene and auxin signaling, respectively, we combined reverse genetic approaches, physiological methods, transactivation experiments and electrophoretic mobility shift assays. Sl‐ERF.B3 is responsive to both ethylene and auxin and ectopic expression of its dominant repressor version ( ERF.B3‐SRDX ) results in impaired sensitivity to auxin with phenotypes recalling those previously reported for Sl‐IAA27 downregulated tomato lines. The expression of Sl‐IAA27 is dramatically reduced in the ERF.B3‐SRDX lines and Sl‐ERF.B3 is shown to regulate the expression of Sl‐IAA27 via direct binding to its promoter. The data support a model in which the ethylene‐responsive Sl‐ERF.B3 integrates ethylene and auxin signaling via regulation of the expression of the auxin signaling component Sl‐IAA27 . The study uncovers a molecular mechanism that links ethylene and auxin signaling in tomato. Abstract : See also the Commentary on this article byFernie & Alseekh, 219 : 479–481 .